2015
DOI: 10.1016/j.jneb.2015.04.251
|View full text |Cite
|
Sign up to set email alerts
|

Development of Culturally-Relevant Community-Based Workshops for a Mexican-Origin Rural, Low-Income Comparison Group

Abstract: Identify 0,4,12 month assessment outcomes. Description: Lifestyle approach to obesity prevention using a 14 week, 6-session, 2-hour program with continuing at-home activities for cooking, eating and playing together. Evaluation: Physical assessments and surveys, including program evaluation, were conducted using R v3.1.1. Conclusions and Implications: Throughout the study, over 30% of youth and 60% of adults were overweight/ obese (n¼220 dyads; youth mean age¼9.8AE0.6 years). Treatment youth increased program … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…We utilized the participants' definition of community, comunidad, as the parents who attended the workshops. The women were all from Mexico, primarily rural towns of Michoac an (Manzo et al, 2016). Over time our involvement with the community led to additional projects, funded by the University Office of the President, including talleres (workshops) for immigrant men in the community as well as community meetings to address local concerns after the 2016 presidential election (Manzo et al, 2020).…”
Section: Promotoras In the Central Valleymentioning
confidence: 99%
See 2 more Smart Citations
“…We utilized the participants' definition of community, comunidad, as the parents who attended the workshops. The women were all from Mexico, primarily rural towns of Michoac an (Manzo et al, 2016). Over time our involvement with the community led to additional projects, funded by the University Office of the President, including talleres (workshops) for immigrant men in the community as well as community meetings to address local concerns after the 2016 presidential election (Manzo et al, 2020).…”
Section: Promotoras In the Central Valleymentioning
confidence: 99%
“…Beginning in 2011, a group of university‐based researchers obtained United States Department of Agriculture (USDA) funding to develop a community‐engaged project designed to offer “best practice interventions to address overweight and obesity among Mexican origin children in the agricultural heartland of the U.S.—California’s Central Valley” (De la Torre et al, 2013). Randomly selected, the comparison community was not to receive nutrition information; instead, Yvette in her role as the community engagement principal investigator and a postdoctoral scholar at the time (Dr. Rosa Manzo) worked with local promotoras to identify community needs (Manzo et al, 2016; Manzo et al, 2018).…”
Section: Three Case Studies Of Muxeres En Acción For Health Equitymentioning
confidence: 99%
See 1 more Smart Citation
“…The community-based approach to the development and delivery of the workshop proved to be effective for workshop attendees. More specifically, the workshop evaluations indicated that participants were satisfied with the content of the workshops and presentation style [18].…”
Section: Gaining Entrymentioning
confidence: 99%
“…The CBPAR approach that set the stage for this study began with the initial engagement stage in the comparison site of the Niños Sanos, Familia Sana (NSFS) study [17]. The engagement process in the comparison site of the NSFS study consisted in the collaboration of community members to develop psycho-educational workshops [18]. The community-based approach implemented in the comparison site engaged community members and local stakeholders in the identification of the workshop topics.…”
Section: Gaining Entrymentioning
confidence: 99%